Teatro infantil para mejorar las habilidades sociales del niño/a de 5 años del C.E.E. Rafael Narváez Cadenillas, 2019 - Cruz Santos, Tatiana Lilibeth (2019)
The present research entitled: Children's theater to improve the social skills of the 5-year-old children of the Rafael Narvaez Cadenillas Experimental Educational School, 2019 had the purpose of improving the skills of the children in the 5-year-old classroom of the aforementioned kindergarten, through children's theater, giving priority to artistic expression, which allowed the children to improve their social skills. The research was applied with a pre-experimental design, with a single experimental group, applying the corresponding pre-test and post-test, it was carried out with a population of 21 children from the 5-year-old classroom "A" of the Rafael Narvaez Cadenillas Experimental Educational Center, made up of 13 boys and 8 girls, who were also our sample. The results obtained in the pre-test showed that 66.67% of the children were in the deficient level and 33.33% in the fair level with respect to social skills; after applying the children's theater, 90.48% reached a good level and 9.52% a fair level. In addition, it was evident that there is a significant difference of 4.67 average points in the improvement of the skills of the experimental group.